Transcriptome Dynamics of an Oyster Larval Response to a Conspecific Cue-Mediated Settlement Induction in the Pacific Oyster Crassostrea gigas - Mary Grace Sedanza; Jalal Alshaweesh; Yi-Li Gao; Asami Yoshida; Hee-Jin Kim; Kenichi Yamaguchi; Cyril Glenn Satuito (Diversity, 2022)
The molecular mechanisms underlying the conspecific cue-mediated larval settlement in Crassostrea gigas is not yet fully understood. In this study, we described and compared the transcriptomes of competent pediveligers (Pedi) and conspecific cue-induced postlarvae (PL). A total of 2383 candidate transcripts were identified: 740 upregulated and 1643 downregulated transcripts, after settlement. Gene Ontology analysis revealed active chitin binding, calcium ion binding, and extracellular region processes in both stages. Results showed that the differential expression trend of six candidate transcripts were consistent between the quantitative real-time PCR and transcriptome data. The differential transcript expression related to shell formation showed closely linked dynamics with a gene regulatory network that may involve the interplay of various hormone receptors, neurotransmitters, and neuropeptide receptors working together in a concerted way in the Pedi and PL stages. Our results highlight the transcriptome dynamics underlying the settlement of oysters on conspecific adult shells and demonstrate the potential use of this cue as an attractant for wild and hatchery-grown oyster larval attachment on artificial substrates. It also suggests the possible involvement of an ecdysone signal pathway that may be linked to a neuroendocrine-biomineralization crosstalk in C. gigas settlement.